Pengaruh Kecukupan Modal, Penyaluran Kredit dan Efisiensi Operasional pada Risiko Kredit - Indira Pramesti, Ida Ayu Mas; Wirajaya, I Gde Ary (E-Jurnal Akuntansi, 2019)
Banks that have high levels of bad credit, risk bankruptcy. Knowing the factors that influence credit risk will deal with the risk of non-performing loans earlier. The factors studied to determine the effect on credit risk are capital adequacy, credit distribution, and operational efficiency. By using a purposive sampling method to determine the sample, a sample of 120 companies with a period of 3 years of observation, namely 2015 to 2017, obtained 1440 observation samples. Multiple linear regression is a data analysis technique used. The results obtained after conducting the analysis are capital adequacy, credit distribution, and operational efficiency have a positive influence on credit risk. Keywords : Capital Adequacy, credit distribution, operational efficiency, credit risk.